Patterns of Z chromosome divergence among Heliconius species highlight the importance of historical demography (2018)
Sex chromosomes are disproportionately involved in reproductive isolation and adaptation. In support of such a “large-X” effect, genome scans between recently diverged populations and species pairs often identify distinct patterns of divergence on the sex chromosome compared to autosomes. When measures of divergence between populations are higher on the sex chromosome compared to autosomes, such patterns could be interpreted as evidence for faster divergence on the sex chromosome, that is “faster-X”, barriers to gene flow on the sex chromosome. However, demographic changes can strongly skew divergence estimates and are not always taken into consideration. We used 224 whole-genome sequences representing 36 populations from two Heliconius butterfly clades (H. erato and H. melpomene) to explore patterns of Z chromosome divergence. We show that increased divergence compared to equilibrium expectations can in many cases be explained by demographic change. Among Heliconius erato populations, for instance, population size increase in the ancestral population can explain increased absolute divergence measures on the Z chromosome compared to the autosomes, as a result of increased ancestral Z chromosome genetic diversity. Nonetheless, we do identify increased divergence on the Z chromosome relative to the autosomes in parapatric or sympatric species comparisons that imply postzygotic reproductive barriers. Using simulations, we show that this is consistent with reduced gene flow on the Z chromosome, perhaps due to greater accumulation of incompatibilities. Our work demonstrates the importance of taking demography into account to interpret patterns of divergence on the Z chromosome, but nonetheless provides evidence to support the Z chromosome as a strong barrier to gene flow in incipient Heliconius butterfly species. © 2018 The Authors. Molecular Ecology Published by John Wiley & Sons Ltd